Feasibility of early postoperative bladder catheter removal without prior bladder-training exercises after laparoscopic nerve sparing radical hysterectomy. (18th August 2019) - Gaballa, Khaled; Denewer, Adel; Khater, Ashraf; Gallotta, Valerio; Conte, Carmine; Federico, Alex; Elfeki, Hossam; Scambia, Giovanni
Abstract: The aim of the study is to evaluate the feasibility of early postoperative bladder catheter removal without prior bladder-training exercises after laparoscopic nerve sparing radical hysterectomy (LNSRH). The post-operative bladder catheterisation period of 30 patients who underwent LNSRH at two institutes in Egypt and Italy were prospectively evaluated with postoperative drainage of the bladder through a Foley catheter for two days without performing bladder-training exercise. The median duration for postoperative bladder catheterisation was 3.5 (3–5) days. Within the fifth postoperative day, 82.7% had a PVR urine volume less than 100 ml. None of the patients had PVR urine more than 100 ml more than 10 days after the operation with no need for self-catheterisation. These results support early postoperative bladder catheter removal without prior bladder-training exercises following LNSRH. IMPACT STATEMENT: What is already known on this subject ? Bladder-training exercise was used routinely following radical hysterectomy (RH) operations before bladder catheter removal. Only two studies reported that these exercises could be omitted, but one study was done on both laparoscopic and open RH patients and the other did not show whether the operation was nerve-sparing and whether it was done by laparoscopy or open technique. What the results of this study add? This study's results support early postoperative bladder catheter removal without prior bladder-training exercises after laparoscopic nerve sparing RH. What the implications are of these findings for clinical practice and /or further research? Excluding the unnecessary procedure of bladder training, which is time- and effort-consuming, after the operation.